2018
DOI: 10.1175/jcli-d-17-0762.1
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation-Induced Land–Atmosphere Feedbacks and Their Impacts on Indian Summer Monsoon

Abstract: From the 1980s, Indian summer monsoon rainfall (ISMR) shows a decreasing trend over north and northwest India, and there was a significant observed reduction in July over central and south India in 1982–2003. The key drivers of the changed ISMR, however, remain unclear. It was hypothesized that the large-scale irrigation development that started in the 1950s has resulted in land surface cooling, which slowed large-scale atmospheric circulation, exerting significant influences on ISMR. To test this hypothesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 50 publications
2
29
1
Order By: Relevance
“…The moisture-budget analysis method has been used in many studies (Chou and Neelin 2004;Chou et al 2009;Seager et al 2010). Here we apply it to understand the physical mechanisms governing historical changes in ISM rainfall.…”
Section: ) Moisture Budget Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The moisture-budget analysis method has been used in many studies (Chou and Neelin 2004;Chou et al 2009;Seager et al 2010). Here we apply it to understand the physical mechanisms governing historical changes in ISM rainfall.…”
Section: ) Moisture Budget Analysismentioning
confidence: 99%
“…For example, warming over the tropical Indo-Pacific warm pool displaces South Asian rainfall with an east-west rainfall shift by inducing anomalous northerlies, which advect drier and cooler air into South Asia (Annamalai et al 2013). Changes in land use and land cover have also been proposed as another contributor: Local evapotranspiration, a source of atmospheric moisture, has decreased as a consequence of deforestation (Paul et al 2016;Chou et al 2018). In addition to the above anthropogenic forcings, a negative-to-positive phase transition from the 1950s to the 1990s of the Pacific decadal oscillation (PDO)/interdecadal Pacific oscillation (IPO), whose recent cycles result mainly from internal variability (Dong et al 2014;Hua et al 2018), also helps to explain the total drying trend over India during this period, as highlighted by Salzmann and Cherian (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown irrigation's impacts on local, regional, and global climate, and even the atmospheric circulation changes (e.g. [10][11][12][13][14][15]). While deforestation usually causes less evapotranspiration and higher temperature, leading to reduced precipitation [16][17][18], precipitation in deforested areas could also be more extensive than that in high-density forests [19].…”
Section: Introductionmentioning
confidence: 99%
“…us, even if the average trend in sea-surface temperature over the Indian ocean is positive, the spatial distribution of trends does not encourage spatially coherent warm sea-surface temperature (SST) or the organized dynamics necessary for the monsoon [32]. It is further complicated by the changes in land use and land cover [33] and increase or decrease in irrigated land in India which can have local as well as remote effects by altering circulations [34] and increasing concentration of greenhouse gases [2][3][4].…”
Section: Temporal Evaluation Of Rainfall and Temperaturementioning
confidence: 99%